The effect of active forces on Wheel Suspension Kinematic Design parameters - Reddy, Chintalapudi Adithya; Venkatesh, Manikanta (My University, 2020)
For passenger cars, passive suspension systems are designed to adapt to a wide range of driving conditions and hence, vehicle suspension design is associated with certain trade-offs between several vehicle attributes (ride comfort and road holding, to name one). Active suspensions however, gives the potential to minimise some of these trade-offs while still being able to adapt to almost all driving conditions. This master thesis work aims at studying the effects of active spring and active damper forces on suspension kinematic parameters through full vehicle simulations. Further, possible modifications to the suspension geometry such as removing antiroll bar component, having a zero anti-geometry (anti-lift, anti-dive and anti-squat) for front and rear suspension and changes to the suspension kinematic targets in the presence of active forces are also investigated. The methodology adapted in the thesis work is an iterative process of comparing the performance of active suspension performance against the passive suspension baseline. This "baseline" performance of the passive suspension system is established by simulating a chosen number of driving maneuvers with a baseline suspension geometry and setup as that of a current production car. The active forces are then introduced in the suspension system and the same chosen number of driving maneuvers are simulated to compare the suspension performance. Further, the third set of simulations are performed for an active suspension system with varied kinematic targets and modifications to suspension geometry. The results from these three sets of simulations are compared, which provides insights to the possible modifications that can be done to the suspension geometry in the presence of active forces. The main outcome is the suspension behavioral patterns in full vehicle simulations with active suspension, with varying parameters of suspension design. The report also details about the results from the driving simulator which are correlated to the simulation results. A case study is discussed in detail towards the final chapters, regarding the effect of active damping forces on vehicle steering demands.
Keywords: active suspension; vehicle attributes; full vehicle simulations; varied kinematic targets